Remediation of the Old Ecological Load in the Protected Area of the Morava River – Re-abandonment of the Oil and Gas Production Wells (Rudarsko-geološko-naftni zbornik, 2022)
The presence of the former oil and gas producing wells that are or can be improperly abandoned creates a possible environmental hazard in terms of contamination of the groundwater and soil in the present. In the area of the Czech Republic, specifically in South Moravia part, which has a long oil and gas production history, plenty of such wells can be found. Finding out the information about their abandonment in archives is often very demanding (sometimes even impossible). During various survey works and re-abandonment attempts it was found out that many wells are originally abandoned improperly, insufficiently or not at all. The occurrence of such wells is not just potential but also very actual hazard for the cultural landscape of the South Moravia, especially for aquifers, agriculture and natural protected areas of national significance. This paper is focused on the possibility of the definitive abandonment of this particular ecological load. The proposed method was verified in laboratory conditions and in the field. It is now a standard form of the re abandonment of oil and gas wells without precise localization in the South Moravian oil fields.